Development of Leadership and Communication Skill Model on Midwifery Students in Physiological Delivery Practice - Sri Utami; Rekawati Susilaningrum; Susilorini Susilorini (Jurnal Ners, 2017)
Introduction: Currently there is a tendency for students only prioritising hard skills without improving their soft skills. This is indicated by the negative attitudes and actions such as delay task submission, bad time management, and a lack of commitment towards a task. The purpose of this research is to find out the model of leadership skill development and communication skill of the vocational Midwifery course.Methods: This study consists of two stages. The research type was observational and explanatory. The first stage used a cross-sectional design and the second stage was quasi-experimental. The subjects of the study for the first stage was 130 respondents, calculated by “rule of the thumb” and by purposive sampling. The second stage consisted of 38 respondents taken by random sampling. The exogenous variables are motivation, self-leadership strategies, job satisfaction, psychological empowerment, self-efficacy, and task commitment. The endogenous variables are leadership skill and communication skills. In the first stage, the data were analysed using PLS and the second stage used a Wilcoxon test with α = 0,05.Results: The variables of motivation, self-leadership and job satisfaction could improve communication skills. In stage 2 (after training), all of the variables increased significantly with p <0,05.Conclusions: Training using the self-leadership module can improve the ability of motivation, self-leadership strategies, job satisfaction, self-efficacy, psychological empowerment, task commitment, communication and student leadership skills.